1993
DOI: 10.1159/000154144
|View full text |Cite
|
Sign up to set email alerts
|

Orosomucoid Polymorphism in Finns, Swedes and Swedish Saamis

Abstract: Genetic polymorphism of orosomucoid (ORM) was studied by isoelectric focusing and immunoblotting in Finns, Swedes and Swedish Saamis. The ORM2 locus was found to be monomorphic in all three ethnic groups. In the Swedish sample the frequency of the ORM1*2 allele (0.414) was within the range found in other European populations, whereas Finns (0.282) and Saamis (0.210) showed significantly lower ORMl*2 frequencies. The extremely low ORM1*2 frequency in the Saamis further underlines the genetic uniqueness of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Saamis tend to differ from other European populations in virtually all genetic marker systems studied [17], and also the difference between Swedish Saamis and Swedes in the MnSOD polymorphism was highly significant (p = 9·10 –6 ). The somewhat higher Ala allele frequency in Finns compared with Swedes may be due to Saamish influence.…”
Section: Resultsmentioning
confidence: 99%
“…Saamis tend to differ from other European populations in virtually all genetic marker systems studied [17], and also the difference between Swedish Saamis and Swedes in the MnSOD polymorphism was highly significant (p = 9·10 –6 ). The somewhat higher Ala allele frequency in Finns compared with Swedes may be due to Saamish influence.…”
Section: Resultsmentioning
confidence: 99%
“…6 On the basis of classical markers, the Sami Here, we present an analysis of the complete mtDNA genome from the northern and southern Swedish Sami groups, with the purpose of studying the genetic structure of the populations and addressing the origin of the Sami people.…”
Section: Introductionmentioning
confidence: 99%
“…ORM1 S has also been classified as ORM1 S2 (T) and ORM1 S2 (C) according to the presence of T or a C at nt 3626 (Yuasa et al, 2006), which is of interest because this change was observed in a Ghanaian family; a low frequency of allele S2 has been described in some Asiatic, Finns, and Swedish groups (Fan et al, 1993), and the study of Mexican subjects did not reveal the presence of this ORM1 S2 polymorphism. Therefore, further studies are needed in order to demonstrate whether these gene arrangements may distinguish other world populations or specific ethnic groups, including Amerindians.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the frequency of ORM1 S is high in Europe, and low in some Asian groups Li et al, 1999). These genetic landmarks, including the F and S phenotypes, differ among ethnic groups, including native populations in Asia, Africa, Europe, and America (Johnson et al, 1969;Fan et al, 1993).…”
Section: Introductionmentioning
confidence: 96%